Some factors affecting birth weight of Brownsindhi cattle (Brown Swiss x Red Sindhi cross) - Umar, H. A.; Shuaibu, A.; Tijjani H. U.; Ma’aruf, B. S.; Umar, M. M. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
The study was conducted to investigate the effects of some factors on birth weight and gestation length of Brownsindhi cattle. A total of 250 cows were used for the study to determine the influence of sex, age at first service and gestation length on this trait (birth weight). Influence of calf’s sex on gestation length was also assessed. Data generated were subjected to analysis of variance using the general linear procedure of SPSS, version 23 (2015). Significantly different means were compared using Least Significant Difference (LSD). The relationship between birth weight and gestation length was estimated using Pearson’s correlation and simple linear regression analyses of the same software. The overall mean birth weight and gestation length were 23.40±0.43 kg and 286.51±0.55 days, respectively. Significant effects of sex (P<0.05) and gestation length (P<0.001) were observed on birth weight. Male calves were heavier at birth than females and higher value for this trait (birth weight) was observed in calves with longer gestation length (291- 295 days). A significant effect of sex on gestation length (P<0.01) was noticed. Males had longer gestation length than females. Significant interaction effect of sex and gestation length on birth weight (P<0.05) was also evident. Males were heavier at birth with longer gestation length than females. The correlation coefficient (R) observed between birth weight and gestation length was high, positive and significant (0.49; P<0.01), while the prediction accuracy (R2) between the two traits was low. Conclusively, sex had effect on weight of calves at birth and that this trait cannot be predicted by the gestation length.